Workshop Public Speaking: To Be A Powerful Public Speaker - Sy. Nurul Syobah; Lukman Nurhakim; Mazidatus Sa’adah; Meilita Aullia Putri; Mona Tindas Gustiana; Rini Lestari; Riswan Riswan; A. Rivai Beta (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The workshop "To Be A Powerful Public Speaker" is designed to improve the public speaking skills of SMA Negeri 14 Samarinda students, especially new members of the Student Council. This activity aims to increase confidence, mastery of communication techniques, and interaction with the audience. The training method includes theory, practice, and evaluation, involving speakers with various topics, such as the basics of public speaking, speaking techniques in broadcasting, and tips for becoming a professional MC. The training results showed that 85% of participants felt more confident in public speaking, increased mastery of intonation and gestures, and the ability to build better relationships with the audience. The hands-on and practical approach to this training ensures that participants understand the theory and can apply it in real life, particularly in their leadership roles. These workshops positively impact students' communication skills, supporting their personal and professional development.